Problems Raised by DAC 6 concerning Taxpayer’s Rights and Fundamental Freedoms. Particular Reference to DAC 6 Implementation in the Spanish Legal Order - Barreiro Carril, María Cruz (Challenges of Contemporary Tax Law: Jubilee Book Dedicated to Professor Włodzimierz Nykiel. Volume II, 2024)
This work aims to identify some of the problems that the Directive 2018/822 of 25 May 2018 amending Directive 2011/16/EU as regards mandatory automatic exchange of information in the field of taxation in relation to reportable cross-border arrangements (DAC 6) and its implementation into the Spanish legal order, raise as regards taxpayers’ rights and fundamental freedoms. By describing the basic content of this reporting obligation, the author emphasizes the vagueness in which that content is defined both in the Directive and in the domestic legislation implementing the Directive, which raises issues as regards the principles of legality, characterization, and legal certainty. Furthermore, the author stressed that the mandatory disclosure regime laid down in the Directive, and in the domestic legislation, shows problems of incompatibility with the EU legal order. The work ends with some general comments on the problem that the Directive raises for taxpayers’ rights from a broader perspective: the one related to the Directive’s legal bases. This perspective helps to understand why, in the author’s opinion, DAC 6 raises also issues concerning fundamental freedoms.